2014
DOI: 10.1614/ws-d-14-00046.1
|View full text |Cite
|
Sign up to set email alerts
|

A Simple In-Season Bioassay for Detecting Glyphosate Resistance in Grass and Broadleaf Weeds Prior to Herbicide Application in the Field

Abstract: The implementation of a successful glyphosate resistance management strategy requires a simple and cost-effective method for detecting resistance in key weeds. To date, however, glyphosate resistance is still routinely confirmed via laborious and time consuming whole-plant pot assays using seeds collected at the end of the growing season. Here, we describe a simple, early-season bioassay for detecting evolved glyphosate resistance in grass and broadleaf weeds. It involves transplanting suspected glyphosate res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
0
16
1
Order By: Relevance
“…], hood canarygrass ( Phalaris paradoxa L.), and green foxtail [ Setaria viridis (L.) Beauv]. Since initial development, this agar-based test has been found to be effective for detecting both target and non–target site resistance in an array of broadleaf and grass weeds of cropping systems (Jackson et al 2015; Kaundun et al 2014).…”
mentioning
confidence: 99%
“…], hood canarygrass ( Phalaris paradoxa L.), and green foxtail [ Setaria viridis (L.) Beauv]. Since initial development, this agar-based test has been found to be effective for detecting both target and non–target site resistance in an array of broadleaf and grass weeds of cropping systems (Jackson et al 2015; Kaundun et al 2014).…”
mentioning
confidence: 99%
“…Based on the plant growth response (root or shoot) in herbicide media, the diagnostic process could be done within 1 wk. Tal et al (2000) reported a seed-bioassay to detect grass weeds resistant to ACCase inhibitor herbicides within 7 d. An agar-based Syngenta quick test has also been developed to detect glyphosate resistance in grass and broadleaf weeds species within 2 wk (Kaundun et al 2014). Although the seed-bioassay provided an effective and early-season resistant diagnosis in a short period of time, it has been difficult to exclude ungerminated seeds because of dormancy, resulting in an underestimation of the germination rate.…”
mentioning
confidence: 99%
“…In similar studies of seedlings tests conducted for other species and herbicides, the successful discrimination between resistant and susceptible biotypes was also reported. In studies with Lolium species, the resistance to glyphosate evaluated with seedlings grown in agar containing herbicide could be identified within 2 wk (Kaundun et al 2014). An assay for discrimination of glyphosate resistance in Lolium multiflorum was developed using tillers with roots (Ghanizadeh et al 2015).…”
mentioning
confidence: 99%
“…Similar research was done by Brosnan et al [34], he found that the quick test using agar medium can be used to determine the resistance of 5-enolpyruvylshikimate-3-phosphate (EPSP) and ALS inhibitor herbicides in Poa annua in less than two weeks. Kaundun et al [35] described a simple, early-season experiment for detecting glyphosate resistance in monocots and dicots weed, he transplanted suspected seedlings alongside known sensitive and resistant standards into agar containing a range rate of herbicide and estimated the percentage survival species after 14 d of plating. Overall, the results of current experiment showed that resistance to ACCase herbicides (post and pre-emergence) can be detected using seed of grass weeds in agar medium.…”
Section: Resultsmentioning
confidence: 99%